2018
DOI: 10.1002/jcb.27416
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal cancer lymph node metastasis–associated gene signature optimizes overall survival prediction of esophageal cancer

Abstract: Esophageal cancer (EC) is characteristic of early regional lymph node metastasis (LNM) and most patients with metastasis have a poor prognosis. However, the current diagnostic techniques do not enable precise differentiation of EC LNM, prognostic stratification, and individual survival estimation. To identify potential molecular biomarkers for EC patients with LNM, we explored differently expressed genes in The Cancer Genome Atlas database between 77 non‐LNM cases and 88 LNM cases by limma package R. Then, acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 36 publications
0
11
0
Order By: Relevance
“…Univariate Cox regression was used for preliminary identification of prognostic DEGs ( Wu et al, 2020 ), followed by multivariate analysis to estimate the prognostic value of the identified DEGs ( Zhang R. et al, 2020 ). To construct a risk assessment system, the risk score for each patient was calculated according to regression coefficients and mRNA expression levels ( Cai et al, 2019 ). Based on the median risk score, patients were allocated to high- and low-risk groups ( Qian et al, 2020 ).…”
Section: Functional Enrichment Analysis Of 342 Intersecting Genesmentioning
confidence: 99%
“…Univariate Cox regression was used for preliminary identification of prognostic DEGs ( Wu et al, 2020 ), followed by multivariate analysis to estimate the prognostic value of the identified DEGs ( Zhang R. et al, 2020 ). To construct a risk assessment system, the risk score for each patient was calculated according to regression coefficients and mRNA expression levels ( Cai et al, 2019 ). Based on the median risk score, patients were allocated to high- and low-risk groups ( Qian et al, 2020 ).…”
Section: Functional Enrichment Analysis Of 342 Intersecting Genesmentioning
confidence: 99%
“…Genes and proteins related to DNA repair have become therapeutic targets in prostate cancer and ovarian cancer [13,14]. For the recent study, plenty of gene sets have been reported as a guidance in optimizing the treatment and play an important role as a biomarker in various cancers [15][16][17][18][19]. Multigene prognostic signatures from tumor tissue of patients can predict the prognosis of cancer patients more accurately than a single gene.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Xue et al searched for key factors by constructing a specific competitive endogenous RNA network in ESCA [9]. The 8-mRNA-based risk score model developed by Cai et al successfully predicted the survival of ESCA [10]. Ushiku et al confirmed that promoter DNA hypermethylation of CDO1 could be an independent prognostic factor in ESCC [11].…”
Section: Introductionmentioning
confidence: 99%